Effect of High-Intensity Interval Training on Physical Health in Coronary Artery Disease Patients: A Meta-Analysis of Randomized Controlled Trials - Litao Du (MDPI AG, 2021)
The effects of exercise-based cardiac rehabilitation (CR) on physical health in coronary artery disease (CAD) patients has long been established, while the optimal exercise mode remains to be determined. This meta-analysis compared the efficacy of high-intensity interval training (HIIT) versus moderate-intensity continuous training (MICT) in CAD patients. Databases were searched up to December 2020. Twenty-five studies with 1272 participants were analyzed. The results showed that both HIIT and MICT induced significant VO2peak improvement with a 4.52 mL/kg/min (p < 0.01) and 2.36 mL/kg/min (p < 0.01), respectively. Additionally, a larger improvement of VO2peak (1.92 mL/kg/min, p < 0.01) was observed in HIIT over MICT. HIIT with medium and long intervals, higher work/rest ratio induced larger VO2peak improvement than the compared subgroup. Interestingly, non-isocaloric exercise protocols induced larger VO2peak improvement compared with isocaloric protocols. In addition, both HIIT and MICT significantly increased anaerobic threshold and peak power with HIIT superior to MICT. No significant different changes were observed in blood pressure after HIIT or MICT intervention, however when HIIT was compared with MICT, MICT seems superior to HIIT in reducing systolic blood pressure (−3.61 mmHg, p < 0.01) and diastolic blood pressure (−2.37 mmHg, p < 0.01). Although, HIIT and MICT induced significant improvement of most other parameters, like HRrest, HRpeak, left ventricular ejection fraction (LVEF), quality of life (QoL), no significant differences were noted between groups. This meta-analysis suggested that HIIT is superior to MICT in increasing VO2peak, anaerobic threshold, peak power in CAD patients. Additionally, the efficacy of HIIT over MICT in improving VO2peaks was influenced by HIIT intervals, work/rest ratio and total caloric consumption. Both HIIT and MICT did not significantly influence resting BP, however, MICT seemed to be more effective in reducing BP than HIIT. HIIT and MICT equally significantly influenced HRrest, HRpeak, HRR1min, OUES, LVEF%, QoL.